PA06 コレステロール誘導体を側鎖に持つキラルスメクチックA液晶エラストマーの相転移と電界誘起変形(液晶物理・物性,ポスター発表,2015年日本液晶学会討論会) - 橋本, 常弘; 樫村, 尚; 平岡, 一幸; 金島, 清太 (Proceedings of Japanese Liquid Crystal Society Annual meeting, 2015)
Liquid crystalline elastomers have been paid increasing attention as ideal materials for the investigation of piezoelectric and inverse-piezoelectric effects, because the polymer network prevents macroscopic flow which disturbs the emergence of piezoelectricity in conventional low-molar-mass liquid crystals. In this report, we focus on the chiral smectic A (SmA*) phase in which the electroclinic effect, namely the direct coupling of molecular tilt to the applied electric field, is expected. Mechanical response to electric stimulation in a side-chain SmA* elastomer is investigated. An elastomer was synthesized by a hydro-silylation reaction of liquid-crystalline side groups with a polysiloxane backbone. Undecylenic acid cholesteryl ester and undecylenic acid 4-undec-10-enoyloxy-phenyl ester were used as mesogenic monomer and crosslinker respectively. The elastomer showed the following phase sequence upon heating: [g 35 SmA* 130 I (in °C)]. Shear deformation, which occurs parallel to the layers and perpendicular to the direction of an applied electric field, is clearly observed above the glass transition temperature, although no mechanical response to electric stimulation is recognized at room temperature because of the glass state. The amplitude of the shear deformation slightly increases with increasing temperature in the temperature region of the SmA* phase. A direction of shear deformation depends of the polarity of the applied electric field. It means that the shear deformation is caused by the electroclinic effect which is caused by a direct coupling between polarization and electric field.